Lynen Lecture - Miami 1974. I Hate to Bore People with my Recollections. (Versión 3) - Leloir, Luis Federico (1974)
Versión publicada: Leloir, Luis F. I Hate to Bore People with my Recollections. EN: Miami Winter Symposia. The Fifth Feodor Lynen Lecture. Biology and Chemistry of Eukaryotic Cell Surfaces / C.Y. Lee and E.E. Smith (eds.); Vol.7. New York: Academic Press, 1974. Pp: 1-20. https://doi.org/10.1016/B978-0-12-441550-8.50006-9